Bond scheme for common agricultural policy [ - Swinbank, A. [ (Alan)]; Tranter, R. B. (CABI, 2004)
"This book demystifies the bond scheme proposal and explores concerns expressed by farmers and policy makers. It reports on a major survey - undertaken in Germany, Portugal and the UK - of farmers' likely reaction to the introduction of a bond scheme, similar partially decoupled payments such as the new Single Payment Scheme introduced by the Fischler reforms. Written by economists, a political scientist and a former Minister of Agriculture, it offers rare insights into EU farm policy and will be of significant interest to policy makers and students in agricultural economics and European studies."--Jacket.